Childhood-Onset Movement Disorders Can Mask a Primary Immunodeficiency: 6 Cases of Classical Ataxia-Telangiectasia and Variant Forms - Blanchard-Rohner, Geraldine; Peirolo, Anna; Coulon, Ludivine; Korff, Christian; Horvath, Judit; Burkhard, Pierre R.; Gumy-Pause, Fabienne; Ranza, Emmanuelle; Jandus, Peter; Dibra, Harpreet; Taylor, Alexander Malcolm R.; Fluss, Joel (Frontiers in Immunology, 2022)
Ataxia-telangiectasia (A-T) is a neurodegenerative and primary immunodeficiency disorder (PID) characterized by cerebellar ataxia, oculocutaneous telangiectasia, immunodeficiency, progressive respiratory failure, and an increased risk of malignancies. It demands specialized care tailored to the individual patient’s needs. Besides the classical ataxia-telangiectasia (classical A-T) phenotype, a variant phenotype (variant A-T) exists with partly overlapping but some distinctive disease characteristics. Here we present a case series of 6 patients with classical A-T and variant A-T, which illustrates the phenotypic variability of A-T that can present in childhood with prominent extrapyramidal features, with or without cerebellar ataxia. We report the clinical data, together with a detailed genotype description, immunological analyses and related expression of the ATM protein. We show that the presence of some residual ATM kinase activity leads to the clinical phenotype variant A-T that differs from the classical A-T. Our data illustrate that the diagnosis of the variant form of A-T can be delayed and difficult, while early recognition of the variant form as well as the classical A-T is a prerequisite for providing a correct prognosis and appropriate rehabilitation and support, including the avoidance of diagnostic X-ray procedures, given the increased risk of malignancies and the higher risk for side effects of subsequent cancer treatment.